Partisipasi Pelaku Ekowisata Dalam Upaya Konservasi di Taman Nasional Tanjung Puting Kalimantan Tengah - Belinda Hastari; Sahat Raja Marigo Girsang (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2019)
Ecotourism is responsible travel journey towards environmental sustainability and well being of local communities. The purpose of this reseach was to describe the participation of ecotourism actors on conservation activity at STPN region III Tanjung Harapan, Tanjung Puting National Park . This research is a combination of a qualitative descriptive and quantitative methods with the respondent survey, and skoring analysis methods. The result showed that the value of participation of ecotourism actors is 1.486 which is categorized as medium participation level. The level of participation for conservation efforts by ecotourism actors has been good, they are awareness about conservation likely silence on feeding area, not disposing of waste and taking forest resources, and involvement in ecotourism activities. It is important to increase conservation campaigns through ecotourism and conservation education for ecotourims actors